A Fixed Capital Model with Transferable and Jointly Utilized Machines in the Sraffa Framework. (11th March 2015) - Huang, Biao
ABSTRACT Fixed capital is treated as a special case of joint production in the Sraffa framework. Much of the literature excludes transferable old machines. Salvadori (1999) builds a model with transferable non‐jointly utilized machines whose efficiency paths are independent of the sectors in which the machines are used. He shows that the neat properties of the non‐transferable single machine model still hold. In an earlier paper, Salvadori (1988a) builds another model with non‐transferable jointly utilized machines. This paper synthesizes these two models. It shows that the properties of the non‐transferable jointly utilized machines model still hold if some conditions are satisfied.